Analisis Penggunaan Kohesi Leksikal pada Teks Cerita Pendek Siswa Kelas XI SMA Negeri 4 Bogor - Suhendra Suhendra; Alma Patriani R (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, UNPAK, 2021)
This research aims to describe the use of types of lexical cohesion tools in short story texts of eleventh grade SMA Negeri 4 Bogor. The method in this research is descriptive qualitative method. The data collection technique in this research is literature study. The validity checking of the data in this study used triangulation. The source of this research is short story text of eleventh grade SMA Negeri 4 Bogor. The focus of lexical cohesion tool in this research are repetition, synonym, antonym, hyponym, collocation, and equivalence. Based on the results of data analysis found 140 lexical cohesion tools were used. The first number of findings, the use of reps was 36 findings (26%). The tool of lexical cohesion was found in repetition of incomplete words in person pronouns, whole words in person pronouns, and whole words in time adverbs. Second, it is synonymous with a total of 14 findings (10%). In general this cohesion tool was found by looking at the form of language whose meaning is similar or similar to other forms of language. Third, antonym with a total of 24 findings (17%). This cohesion tool can be identified by looking at words that have different meanings in other words. Fourth, hyponym with a total of 10 findings (7%). Hyponyms are related to words that have a narrower meaning and are covered in the meaning of one more general word. Fifth, 24 collocations were found (17%). Collocation, related to the relationship of words and other words in the same environment. Finally, equivalence with a total of 32 findings (23%). The tool for lexical cohesion in general, deals with the use of meaning that is very close because of the use of the same basic words. Thus, from this number it can be concluded that in the short story students found many uses of lexical cohesion tools from 25 short stories found as many as 140 data findings and the use of the most dominant lexical cohesion tool found in the use of repetition with data findings of 26% data. Repetition is widely used by students to express affirmation of the object being told. In addition, the cohesion tool is also used with the intention of repetition with the replacement of the word referenced by the word that replaces it.